2006
DOI: 10.1515/znb-2006-0108
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Zinc Chloride / Methyl(2-pyridyl)ketone Oxime Reaction System: A Mononuclear Complex and an Inverse 12-Metallacrown-4 Cluster

Abstract: The reactions of methyl(2-pyridyl)ketone oxime, (py)C(Me)NOH, with zinc chloride have been investigated. An excess of the ligand in EtOH/MeCN affords the mononuclear complex [ZnCl 2 {(py)C(Me)NOH} 2 ] (1) in moderate yield. The metal ion is coordinated by two chloro ligands and two N, N'-chelating (py)C(Me)NOH molecules. The six-coordinate molecule is the ciscis-trans isomer considering the positions of the coordinated chlorine, pyridyl and oxime nitrogen atoms, respectively. The reaction between equimolar qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 37 publications
0
7
0
2
Order By: Relevance
“…This shift is attributed to the coordination of the oximate nitrogen. 37 The band is strong in the spectrum of the Ni 16 cluster, because it also has a ν 3 (F 2 ) [ν d (SO)] character due to the ionic sulfates (T d symmetry). Somewhat to our surprise, the 1566 cm −1 band is shifted to a higher wavenumber in the complexes (1577 cm −1 in 1•5MeOH, 1580 cm −1 in 2•10H 2 O• 26MeOH), overlapping with an aromatic stretch.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This shift is attributed to the coordination of the oximate nitrogen. 37 The band is strong in the spectrum of the Ni 16 cluster, because it also has a ν 3 (F 2 ) [ν d (SO)] character due to the ionic sulfates (T d symmetry). Somewhat to our surprise, the 1566 cm −1 band is shifted to a higher wavenumber in the complexes (1577 cm −1 in 1•5MeOH, 1580 cm −1 in 2•10H 2 O• 26MeOH), overlapping with an aromatic stretch.…”
Section: Resultsmentioning
confidence: 99%
“…This shift may be indicative of the oximate nitrogen coordination. 37 Extensive studies on Schiff-base complexes (which also contain a CvN bond) have shown 38 that a change in the s character of the nitrogen lone pair occurs upon coordination such that the s character of the nitrogen orbital, which is involved in the CvN bond, increases; this change in hybridization produces a greater CvN stretching force constant relative to the free neutral ligand. The in-plane deformation band of the 2-pyridyl ring of free pyaoxH 2 at 632 cm −1 shifts upwards in 1•5MeOH (646 cm −1 ) and 2•10H 2 O•26MeOH (645 cm −1 ), confirming the involvement of the ring-N atom in coordination.…”
Section: Resultsmentioning
confidence: 99%
“…The 1.011 ligation mode is the exclusive one for the metal complexes containing the neutral ligand [22, 24, 30]. …”
Section: Resultsmentioning
confidence: 99%
“…Thus, (py)C(R)NOH behave as N , N ' -chelating ligands (see Scheme 2) making necessary the employment of additional inorganic or organic anions to complete the coordination sphere of the metal centre or to balance the charge of the complex cation. A variety of mono anions have been used for this reason, for example, PhCO 2 − [21], Cl − [22, 23], Br − [24], and NO 3 − [25]. Recently, we have started a research program to explore the use of the sulfate ion, SO 4 2− , in 3d-metal/2-pyridyl oxime chemistry, instead of the abovementioned mono anionic ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Somewhat to our surprise, the 1568 cm −1 band is shifted to a higher wavenumber in the complex (1598 cm −1 ), overlapping with an aromatic stretch. This shift may be indicative of the oxime nitrogen coordination [94]. Extensive studies on Schiff base complexes (which also contain a C=N bond) have shown [95] that a change in the s character of the nitrogen lone pair occurs upon coordination such that the s character of nitrogen orbital involved in the C=N bond increases; this change in hybridization produces a greater C=N stretching force constant relative to the free neutral ligand.…”
Section: Ir Spectramentioning
confidence: 99%